2004
DOI: 10.1016/j.jacc.2004.06.073
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of plasma from patients during an acute coronary syndrome

Abstract: Plasma proteomic analysis makes it possible to develop a map of the protein isoforms that are expressed in plasma during an ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
1
9

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(140 citation statements)
references
References 25 publications
2
128
1
9
Order By: Relevance
“…Interestingly, apolipoprotein C-I and C-III appeared to be the first reported plasmatic biomarkers able to accurately distinguish between ischemic and hemorrhagic stroke within a small number of patients [72]. Proteomic analysis of plasma from patients suffering from acute myocardial infarction revealed also modifications of the protein pattern different from that of patients with unstable angina [73]. Proteomics has allowed the detection of drug-induced toxicity, and toxicoproteomics has developed [74].…”
Section: Clinical Applications -Biomarker Identificationmentioning
confidence: 99%
“…Interestingly, apolipoprotein C-I and C-III appeared to be the first reported plasmatic biomarkers able to accurately distinguish between ischemic and hemorrhagic stroke within a small number of patients [72]. Proteomic analysis of plasma from patients suffering from acute myocardial infarction revealed also modifications of the protein pattern different from that of patients with unstable angina [73]. Proteomics has allowed the detection of drug-induced toxicity, and toxicoproteomics has developed [74].…”
Section: Clinical Applications -Biomarker Identificationmentioning
confidence: 99%
“…This fibrinogen γ chain isotype 1 has also been found increased in patients during an acute coronary syndrome. 11 In this regard, fibrinogen participates in platelet aggregation and inflammation. A different alternative splicing of fibrinogen γ chain messenger ribonucleic acid has recently been demonstrated that results in fibrinogen γ chain variants that alter fibrin formation and structure and could be associated with an increase of thrombotic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Como se ha publicado previamente (135), las muestras se redujeron con ditioeritritol Mediante un pulsador se selecciona un determinado ion padre y sus iones fragmento, que son acelerados a un potencial mayor y separados en el segundo TOF.…”
Section: A10unclassified
“…Con el análisis en modo MS obtuvimos un espectro de masas denominado "huella peptídica" (Fig. 4.5), y algunos de los péptidos observados se analizaron en modo MS/MS, como se ha publicado anteriormente (135). El modo MS/MS obtiene espectros de fragmentación de las 3-5 masas mayoritarias dentro de cada una de las huellas peptídicas.…”
Section: A10unclassified